KESESUAIAN LAHAN JENIS POHON MANGROVE DI BULAKSETRA, PANGANDARAN JAWA BARAT Land Suitability Mangrove Trees Species in Bulaksetra, Pangandaran West Java - Cecep Kusmana; Zulkifli Abidin Chaniago (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2017)
Species site matching activities very useful to support the success of cultivation of the land, because this activity will be known the suitability of a plant species and its environment. Specifically for mangrove, factors that need to be considered to do species site mathing are salinity, frequency of flooding, soil texture and acidity of waters. Mangrove area in Bulaksetra, Desa Babakan Kecamatan Pangandaran Kabupaten Pangandaran on 17th July 2006 ever experienced tsunami disaster. Mangrove forest which is located in that area having damage that result mangrove vegetation on some terrace in that area already lost. Therefore, that area must be rehabilitation so that ecological functions of the area can return. This research was conducted to know mangrove species who suitable to plant in that area, which do the measurement activity mangrove land suitability parameters consisting of salinity, frequency of flooding, soil texture and acidity of waters. Research result provide information that the appropriate species planted in the damaged mangrove areas include Rhizophora apiculata, Rhizophora mucronata, Bruguiera gymnorrhiza, Bruguiera parviflora, Sonneratia alba, Sonneratia caseolaris and Avicennia spp. are major mangrove species and Xilocarpus granatum and Heritiera littoralis are minor mangrove species. Then the dominant vegetation area is Nypa fruticans, the appropriate type among others are Rhizophora apiculata, Rhizophora mucronata, Bruguiera parviflora, Sonneratia alba, and Avicennia spp.Key word: Bulaksetra, land suitability, mangrove, rehabilitation